The Executive Power - Horváth, Attila (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
“The executive power is the moving force of a government. It represents, in the political system, that mysterious principle which, in moral man, unites action to the will”. Although more than 200 years have passed since Jacques Necker, the finance minister for Louis XVI, completed his essay on the executive power, his definition still holds in many respects. However, the term ‘executive’ as the name of a branch of government may be misleading. As Vile notes, the executive “gets its name from one of its major functions, that of putting the law into effect”. It goes without saying that the executive means more than just implementing laws passed by the legislature. Although explaining the concept of the executive and enumerating its task would greatly exceed the scope of this chapter, it is worth recalling some thoughts of Mansfield, who claimed in his seminal work on modern executive power that it is the executive power that made the principle of separation of powers workable. In his view, “for executive power, always ready for emergency, ensured that the power of government was not diminished, much less stalemated, when it was separated into three branches”. His volume revolves around the idea of ambivalence of the modern executive: “The beauty of executive power, then, is to be both subordinate and not subordinate, both weak and strong. It can reach where law cannot, and thus supply the defect of law, yet remain subordinate to law”. The chapter unfold as follows (since the current volume devotes a whole chapter to the powers of the heads of state, this chapter focuses on governments): in the first section, we outline the structure of the executive power in the eight examined states. The second section is devoted to the governments as key actors of the executive power, dealing with their status, composition, competencies and formation while paying special attention to the question of responsibility. The third section briefly outlines the territorial level of the executive. KEYWORDS: executive power, governments, prime ministers, government formation, vote of (no) confidence.